MEMS oxygen transport device for islet transplantation in the subcutaneous site. (1st October 2016) - Komatsu, Hirotake; Kang, Dongyang; Lin, Henry; Cook, Colin A.; Mendez, Daniel; Rawson, Jeffrey; Mullen, Yoko; Kandeel, Fouad; Tai, Yu‐Chong
Abstract : A new microelectromechanical systems (MEMS) oxygen transporter device to improve the efficacy of islet transplantation to treat type 1 diabetes is described here. The device is fabricated for biocompatibility and designed to maintain islet oxygenation levels throughout the normally hypoxic subcutaneous transplant site. Transplantation of the islets and the device to the subcutaneous location is minimally invasive. Bench‐top testing and computational modelling of the device demonstrate that the device can provide sufficient oxygen to prevent hypoxia‐induced islet death transplanted subcutaneously. In vitro studies show that the partial oxygen tension is well‐maintained using the oxygen transporter in an anoxic environment. In vivo studies using a rat subcutaneous transplant model demonstrate that transplanted islets have more than three‐times higher survival using the oxygen transporter compared with transplants not using the transporter, two weeks post‐transplant. In addition, histology sections show well‐maintained islet structures one month after transplantation for islets transplanted in the presence of the device. Our MEMS oxygen transporter is a novel and promising device to support the efficacy of subcutaneous islet transplantation as a potential cure for type 1 diabetes.